2021
DOI: 10.3390/ijerph182312530
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Prevalence of Birth Defects between Newborns of Immigrant and Native-Born Mothers in Taiwan: Ten Years of Population-Based Data

Abstract: In recent years, newborns born to immigrant mothers have accounted for about 10% of the total births in Taiwan. However, little is known about whether there are differences between newborns of immigrant and native-born mothers regarding the prevalence and the possible causes of birth defects. By combining four nationwide databases and assessing all newborns between 2005 and 2014 in Taiwan as research subjects, this study determined the prevalence of birth defects stratified into nine categories (neuronal, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Similar to paternal age, maternal household registration as an indicator has rarely been addressed in previous studies. Yu-Jung et al found that the prevalence of birth defects in newborns of immigrant mothers was lower than that of native-born mothers in Taiwan [ 39 ]. In contrast, Anne-Marie et al found a higher risk of congenital anomalies in migrants in Europe [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to paternal age, maternal household registration as an indicator has rarely been addressed in previous studies. Yu-Jung et al found that the prevalence of birth defects in newborns of immigrant mothers was lower than that of native-born mothers in Taiwan [ 39 ]. In contrast, Anne-Marie et al found a higher risk of congenital anomalies in migrants in Europe [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…BDs were diagnosed by physical examination, ultrasonography, X-ray examination, and/or genetic diagnostic methods, based on the Chinese National Criteria of Birth Defects and Tiny Deformities and the clinical modification codes as congenital malformations, deformations, and chromosomal abnormalities (codes Q00–Q99) of ICD-10 ( 1 , 6 , 10 ). Experts from each registered hospital were responsible for the diagnostic confirmation and provision of technical support.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we first classified BDs based on the ICD-10 system to better understand the epidemiological characteristics of BDs ( 1 , 10 ). Thus, nine categories were involved in the classification as the research outcome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration is motivated by a variety of factors, including marriage, family expansion, economic ambitions, and a variety of personal goals. Intermarriages in Taiwan began growing in 1983 and peaked in 1992, with miscegenation declining since the peak (Zhuang, 2010;Chen, 2019;Lin et al, 2021). The majority of migrant women marry working-class or farmer men in Taiwan (Yu, 2022).…”
Section: Introductionmentioning
confidence: 99%